The Implementation of Assemblr Augmented Reality in Teaching English Vocabulary Mastery to Deaf Students (Pusat riset dan Inovasi Nasional, 2026)
This study examines the effectiveness of Assemblr Augmented Reality (AR) in improving English vocabulary mastery among deaf students in an inclusive classroom setting. The research was conducted at SD N 2 Bengkala using a quantitative pre-experimental design with a one-group pre-test and post-test approach. The participants were Grade 5 deaf students selected through purposive sampling. Data were collected using a researcher-developed vocabulary test consisting of 15 items, which was validated through expert judgment and demonstrated high reliability (Cronbach’s Alpha = 0.815). Descriptive statistical analysis revealed a substantial improvement in students’ vocabulary scores, with the mean increasing from 45.00 in the pre-test to 76.50 in the post-test. The minimum score improved from 40 to 73, and the maximum score increased from 50 to 80. Inferential analysis using the Wilcoxon Signed-Rank Test showed a significance value of 0.180, indicating no statistical significance due to the small sample size. However, the observed improvement indicates strong practical significance. The findings suggest that Assemblr AR enhances vocabulary learning by providing visual and interactive learning experiences that support deaf students’ cognitive processing. This study highlights the potential of AR technology as an effective instructional medium in inclusive education environments.